Twenty four hour oesophageal acidity in achalasia before and after pneumatic dilatation. Issue 7 (July 1987) - Smart, H L; Foster, P N; Evans, D F; Slevin, B; Atkinson, M
Abstract : Radiotelemetric ambulatory 24 hour oesophageal pH measurement was carried out in 17 patients with symptomatic manometrically proven achalasia before and after pneumatic dilatation. Before dilatation an abnormally high percentage acid exposure time was present but typical episodes of gastro-oesophageal reflux occurred in only one patient. In nine patients who had a oesophageal food residue these values were significantly greater than those found in the remaining patients without retained food. Analysis of oesophageal food residues revealed that the low pH was predominantly caused by lactic acid. These findings indicate that preoperative oesophageal pH studies do not offer a valid means of selection of patients in whom an antireflux procedure should be combined with cardiomyotomy. Repeat studies one week after pneumatic dilatation showed a fall in the acid exposure time in patients with initial food residue presumably resulting from improved oesophageal emptying after treatment. A significant rise in acid exposure time after dilatation was seen in those patients without initial food residue presumably resulting from gastro-oesophageal reflux after therapeutic disruption of the lower oesophageal sphincter. Troublesome symptoms of gastro-oesophageal reflux were, however, uncommon after bag dilatation.